Towards implementing a next-generation resource discovery tool: virtual union catalogue of digital repositories in Sri Lanka - Mariyapillai, J.; Gamage, Ruwan (National Institute of Library & Information Sciences (NILIS), University of Colombo, Sri Lanka, 2015)
Information managers have a strategic interest in the tools and technologies that facilitate the discovery and access to the resources for the communities that their serve. Traditional online catalogues, repositories and journals databases provide separate interfaces and platforms for users. In contrast, federated search engines and metadata harvesters enable searching from a single interface. This paper documents the success and challenges faced in introducing a virtual union catalogue of repositories...
Keywords: union catalogue; National Digital Union Catalogue; metadata harvesting; OAI-MPH; Vufind